Nagorno-Karabakh and Aland Islands cases compared - Makili-Aliyev, Kamal (Contested Territories and International Law, 2020)
The Aland Islands precedent and the Nagorno-Karabakh Conflict have a pronounced number of similarities that lie in: the historical context, positions of the conflicting parties toward the conflict issues, similarity of arguments from the parties to the conflict, involvement of third states as greater powers, legal arguments and their validity and other matters. The comparative analysis will concentrate on specific areas of the Aland Islands precedent and the Nagorno-Karabakh Conflict. This chapter examines the minority issues in each situation in order to see where concerns for minority rights have been satisfied from the point of view of international law and where these rights have suffered in terms of their violation and inapplicability. To begin the analysis with the applicable law that was developing at the same time with the autonomy of the Aland Islands, it seems logical to start with the definition of the minority as a subject of protection in international law.